Use of Artificial Intelligence for Analysis and Dimensioning of Structures in Armed Concrete: a technological prospection - Discher, Marcos Gottschalg (2022)
Artificial Intelligence (AI) is a technology that makes use of machines that learn from experience and have the ability to perform complex tasks such as the design of reinforced concrete structures. The increase in the complexity of structures used in constructions brings the need for the development and implementation of new technologies in civil construction. Thus, the objective of this work was to carry out a scientific and technological prospection on the use of AI in the analysis and design of reinforced concrete structures. This work presents a qualitative-quantitative approach, of an exploratory nature, through scientific research in the bases of Capes and Web of Science, and patents in the bases of INPI and Orbit. Although the use of ICTs in civil construction is timid, the prospection pointed to a relevant growth in the use of AI in civil construction in the world, however, in Brazil the use of technology is still very incipient.